Fostering Social Support and Professional Learning for Special Educators: Building a Community of Practice. (June 2023) - Hirsch, Shanna E.; Mathews, Hannah Morris; Griffith, Catherine; Carlson, Alex; Walker, Alexis
Special educators working with students with emotional and behavioral disorders often report experiencing collegial isolation, exclusion from school communities, and high levels of burnout and stress. At the same time, many special educators have limited professional development and networking opportunities, which could mitigate these negative experiences. In response, we adapted Project Extension Community Healthcare Outcomes (ECHO) to connect and support special educators who work with students with emotional and behavioral disorders (EBD). The ECHO model creates a learning loop between a team of specialists and educators. Through participation in the ECHO, educators and specialists engaged in case-based learning and shared best practices for supporting students with EBD. We used a pre–post group design to examine how the ECHO model can address issues related to educator stress and emotional exhaustion while building a community of practice. Though participants agreed that ECHO creates a community of practice and experienced the program as beneficial, we found no statistically significant differences in participants' stress and emotional exhaustion between the pre/post survey. Our findings suggest that brief interventions are insufficient for addressing the complexities of teacher burnout.